行星轮式取盒机构的研究与分析 - 李龙; 曹巨江; 田晓鸿 (Jixie chuandong)
A kind of planet gear style box taking mechanism in automatic cartoner is introduced and analyzed.Its kinematical scheme and working principle are introduced by using the analysis of process motion,the kinematics detailedly analysis is carried out and the key factor which influences the efficiency of box taking is confirmed,and the theoretical basis for mechanism optimization is provided.The structure of the mechanism is compact and easy to manufacture,besides the mechanism runs smoothly and good economic benefits is acquired.